2016
DOI: 10.3389/fncel.2015.00501
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as Novel Regulators of Adult Neurogenic Niches

Abstract: Adult neurogenesis has been convincingly demonstrated in two regions of the mammalian brain: the sub-granular zone (SGZ) of the dentate gyrus (DG) in the hippocampus, and the sub-ventricular zone (SVZ) of the lateral ventricles (LV). SGZ newborn neurons are destined to the granular cell layer (GCL) of the DG, while new neurons from the SVZ neurons migrate rostrally into the olfactory bulb (OB). The process of adult neurogenesis persists throughout life and is supported by a pool of neural stem cells (NSCs), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 381 publications
0
90
0
8
Order By: Relevance
“…These results indicate that Exo-AT contains adipogenic factors that could trigger adipogenic signaling in ADSCs, resulting in adipogenic differentiation. In fact, previous studies have proved that the exosomes derived from osteoblasts, neurons and muscle cells can mediate differentiation of MSCs, although no work had been undertaken on Exo-AT (Narayanan et al, 2016; Cui et al, 2016; Batiz et al, 2015;Choi et al, 2016). Therefore, we conclude that exosomes may serve as a mediator of communication between stem cells and mature tissue cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results indicate that Exo-AT contains adipogenic factors that could trigger adipogenic signaling in ADSCs, resulting in adipogenic differentiation. In fact, previous studies have proved that the exosomes derived from osteoblasts, neurons and muscle cells can mediate differentiation of MSCs, although no work had been undertaken on Exo-AT (Narayanan et al, 2016; Cui et al, 2016; Batiz et al, 2015;Choi et al, 2016). Therefore, we conclude that exosomes may serve as a mediator of communication between stem cells and mature tissue cells.…”
Section: Discussionmentioning
confidence: 89%
“…Although some functions or mechanisms remain elusive, it has been demonstrated that exosomes can modulate their neighboring cells by influencing major cellular process including apoptosis, cell differentiation, proliferation and metabolism (Qin et al, 2016;Braicu et al, 2014). One obvious point about the content of exosomes is that they contain miRNAs, which can inhibit translation of mRNAs by targeting 3′ untranslated regions (UTRs) (Batiz et al, 2015). Transported miRNAs are capable of targeting mRNAs in recipient cells and, hence, are associated with cell-to-cell signaling and communication (He et al, 2014;Valadi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, how these signals are communicated between the fetal and maternal compartments is poorly understood. As intercellular signaling vesicles that can travel long distances through tissues and fluids (Raposo and Stoorvogel, 2013; Mincheva-Nilsson and Baranov, 2014; Bátiz et al, 2015; De Toro et al, 2015), exosomes may be carriers of these signals.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are characterized by their contents, which reflect the physiological status of the origin cell and can regulate the phenotype of the target cell (Kambe et al, 2014; Bátiz et al, 2015; Sheller et al, 2016; Willms et al, 2016). At term, oxidative stress and inflammation build up in the amniotic cavity, causing cellular senescence of the fetal membranes and subsequent release of signals of cellular damage (Menon, 2014; Behnia et al, 2015, 2016; Polettini et al, 2015; Menon et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…These factors can reach distal areas of the brain via bulk flow of the CSF and can act in both an autocrine and paracrine manner [63,137]. In addition to diffusible factors, exosomes containing signaling factors and non-coding (nc) RNAs, such as long ncRNAs and miRNAs, are present in the CSF [11] and can be choroid plexus-derived [6,55]. Finally, the choroid plexuses also contain a large array of enzymes and act as an enzymatic or metabolic barrier, by modulating the activity and availability of neurotransmitters, peptides, growth factors, hormones, drugs and xenobiotics.…”
Section: Source and Regulated Entry Route Of Factors Into The Brainmentioning
confidence: 99%